STUDIES ON THE PATHOGENESIS OF STAPHYLOCOCCAL INFECTION : II. THE EFFECT OF NON-SPECIFIC INFLAMMATION - Goshi, Keiichi (The Rockefeller University Press, 1961)
Studies have been described in which the effect of early and late or established inflammation, upon staphylococcus infection of rabbit skin has been evaluated. Inflammation was produced in skin by thermal, chemical, bacterial and immunological injury, and it was found that the area of inflammation was more susceptible to staphylococcus infection than was normal skin if the bacteria were injected within 2 to 3 days after the injury. When staphylococci were injected into an area of inflammation of over 3 days' duration, there appeared to be an increase in local resistance to infection. The way in which inflammation was produced seemed to have a little influence upon the effects observed. This influence of non-specific inflammation upon staphylococcus infection was compared with the influence of specific bacterial hypersensitivity, which also is associated with an increase in infectivity of the microorganism in sensitized animals. It was concluded that specific bacterial hypersensitivity probably increases susceptibility to infection with the staphylococcus in the same way as non-specific inflammation. The general significance of non-specific inflammation upon infection is also discussed.